Systematics and evolution of gall formation in the plant‐associated genera of the wasp subfamily Doryctinae (Hymenoptera: Braconidae). (26th May 2014) - ZALDÍVAR‐RIVERÓN, ALEJANDRO; MARTÍNEZ, JUAN J.; BELOKOBYLSKIJ, SERGEY A.; PEDRAZA‐LARA, CARLOS; SHAW, SCOTT R.; HANSON, PAUL E.; VARELA‐HERNÁNDEZ, FERNANDO
Abstract Gall formation is a specialised form of phytophagy that consists of abnormal growth of host plant tissue induced by other organisms, principally insects and mites. In the mainly parasitoid wasp subfamily Doryctinae, gall association, represented by gall inducers, inquilines and their parasitoids, is known for species of seven genera. Previous molecular studies recovered few species of six of these genera as monophyletic despite their disparate morphologies. Here, we reconstructed the evolutionary relationships among 47 species belonging to six gall‐associated doryctine genera based on two mitochondrial and two nuclear gene markers. Most of the Bayesian analyses, performed with different levels of incomplete taxa and characters, supported the monophyly of gall‐associated doryctines, with Heterospilus (Heterospilini) as sister group. Percnobracon Kieffer and Jörgensen and Monitoriella Hedqvist were consistently recovered as monophyletic, and the validity of the monotypic Mononeuron was confirmed with respect to Allorhogas Gahan. A nonmonophyletic Allorhogas was recovered, although without significant support. The relationships obtained and the gathered morphological and biological information led us to erect three new genera originally assigned to Psenobolus: Ficobolusgen.n. (F. paniaguaisp.n. and F. jaliscoisp.n.), Plesiopsenobolusgen.n. (Pl. mesoamericanussp.n., Pl. plesiomorphus van Achterberg and Marsh comb.n., and Pl. ticosp.n.), and Sabinitagen.n. (S. mexicanasp.n.). The origin of the gall‐associated doryctine clade was estimated to have occurred during the middle Miocene to early Oligocene, 16.33–30.55 Ma. Our results support the origin of true gall induction in the Doryctinae from parasitoidism of other gall‐forming insects. Moreover, adaptations to attack different gall‐forming taxa on various unrelated plant families probably triggered species diversification in the main Allorhogas clade and may also have promoted the independent origin of gall formation on at least three plant groups. Species diversification in the remaining doryctine taxa was probably a result of host shifts within a particular plant taxon and shifts to different plant organs. This published work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:0021F253‐4ABA‐4EAA‐A7A9‐FC0AD1932EA3